Analysis of heavy metal (Cd, Hg, Fe) contamination in canal water as an environmental challenge - Suma, Fani; Lamangantjo, Chairunnisah J.; Aydalina, Regina Valentina; Zakaria, Zuliyanto; Kumaji, Syam S. (EcoVision: Journal of Environmental Solutions, 2025)
Background: This study aims to determine the quality of water channels close to rice fields and houses that produce domestic and agricultural waste based on heavy metal contamination. Method: Water sampling was carried out directly at the research location and tested at the UPTD Regional Health Laboratory of Gorontalo Province. The sampling points amounted to three points, namely station I, station II, and station III. The water quality parameters analyzed included heavy metals (Cd, Hg, Fe), pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), and temperature. Results: The results of Cd heavy metal concentrations at each point were station I (0 mg/L), station II (0 mg/L), and station III (0 mg/L). Heavy metal Hg was recorded at station I (0.0038 mg/L), station II (0.00185 mg/L), and station III (0 mg/L). Fe heavy metal concentrations were station I (1.20685 mg/L), station II (1.0082 mg/L), and station III (0.4 mg/L). The pH value in Tamalate canal water remained stable at around 7, with station I (7.3), station II (7.4), and station III (7.3). The DO values were station I (82.7 mg/L), station II (85.1 mg/L), and station III (81.7 mg/L). The BOD values were station I (55.35 mg/L), station II (51.85 mg/L), and station III (57.05 mg/L). The COD values were station I (110.5 mg/L), station II (109.5 mg/L), and station III (119.5 mg/L). The temperature measurements were station I (30.95℃), station II (29.35℃), and station III (30.2℃). Conclusion: The distribution of heavy metals in canal water is quite varied due to the influence of environmental conditions and activities around the Tamalate canal, resulting in uneven distribution. Novelty/Originality of this article: This study provides a detailed assessment of heavy metal contamination using multiple water quality indicators. It highlights the influence of surrounding land use, including domestic and agricultural activities, on metal distribution and overall water quality.